Cytotoxic Effects of Srikhandasavam on Ethanol-Induced Neurotoxicity in Hippocampal Cell Cultures - S Kondamma; J. Kalaivannan; Sumathi Jones; C.S. Janaki; Dhastagir Sheriff; K. Prabhu; Deepalakkshmi Balakrishnan; Shyamala Sambasivam (Journal of Pharmacy and Bioallied Sciences)
Background: Srikhandasavam is a traditional Ayurvedic herbal formulation known for its potential therapeutic properties, particularly in enhancing overall vitality and digestive health. It is composed of a blend of natural ingredients, including sandalwood, which are fermented to enhance their medicinal potency. Aim: The present study investigates the neuroprotective effects of Srikhandasavam on hippocampal neurons subjected to ethanol-induced neurotoxicity. Methods: The primary focus was to assess cell viability and cytotoxicity in the presence of Srikhandasavam at various concentrations, using hippocampal cell cultures. Results: The cytotoxicity results indicated a significant impact at higher concentrations, with 50.3% cell mortality observed at 200 µg/mL of Srikhandasavam. Conversely, the MTT assay revealed that Srikhandasavam offered notable protection against ethanol-induced neurotoxicity, with a 71.8% cell viability rate at the same 200 µg/mL concentration. Conclusion: These findings suggest that Srikhandasavam as a potential neuroprotective agent, capable of mitigating ethanol-induced damage in hippocampal neurons while maintaining cell viability at therapeutic concentrations.